1995
DOI: 10.1002/tea.3660320806
|View full text |Cite
|
Sign up to set email alerts
|

An empirical examination of the effects of family commitment in education on student achievement in seventh grade science

Abstract: A national data base from the Longitudinal Study of American Youth (LSAY) was employed to examine the effects of family commitment in education on student achievement in seventh grade science. The backward elimination procedure in the Statistical Analysis System (SAS) was adopted in this study to select significant variables of family commitment at a = .05. The results show that around 22% of the variance in student science achievement can be explained by the selected significant LSAY variables. An analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…Moreover, Henderson (1988) found this holds true across various social, economic, and ethnic backgrounds, which has been confirmed in numerous studies over multiple decades (Alexander, Entwisle, & Horsey, 1997;Casanova, García-Linares, Torre, & Carpio, 2005;Frome & Eccles, 1998;Goyette & Xie, 1999;Hao & Bonstead-Bruns, 1998b;Räty, 2006;Seginer, 1983;Singh, Bickley, Keith, Keith, Trivette, & Anderson, 1995;Steinberg, Lamborn, Dornbusch, & Darling, 1992;Trusty, 2000Trusty, , 2002Trusty & Harris, 1999;Vollmer, 1986;Wang & Wildman, 1995;Wright, Horn, & Sanders, 1997). Parental expectation is routinely defined as the conviction a parent holds in his or her child's future level of achievement.…”
Section: Introduction And/or Review Of the Literaturementioning
confidence: 71%
“…Moreover, Henderson (1988) found this holds true across various social, economic, and ethnic backgrounds, which has been confirmed in numerous studies over multiple decades (Alexander, Entwisle, & Horsey, 1997;Casanova, García-Linares, Torre, & Carpio, 2005;Frome & Eccles, 1998;Goyette & Xie, 1999;Hao & Bonstead-Bruns, 1998b;Räty, 2006;Seginer, 1983;Singh, Bickley, Keith, Keith, Trivette, & Anderson, 1995;Steinberg, Lamborn, Dornbusch, & Darling, 1992;Trusty, 2000Trusty, , 2002Trusty & Harris, 1999;Vollmer, 1986;Wang & Wildman, 1995;Wright, Horn, & Sanders, 1997). Parental expectation is routinely defined as the conviction a parent holds in his or her child's future level of achievement.…”
Section: Introduction And/or Review Of the Literaturementioning
confidence: 71%
“…Parental involvement was also found to play an important role in the development of science attitudes of students (George & Kaplan, 1998;Wang & Wildman, 1995). Shibeci's (1984) work showed among others that science programs affect attitudes inconsistently, the gender is related to attitude [also shown in Koballa's (1993) work], environmental effects are indirect, and biological and physical science attitudes differ.…”
Section: Variables Associated With Attitude Toward Sciencementioning
confidence: 94%
“…Adolescents' educational aspirations relate more to their mother's educational goals for them than to their best friend's goals (Steinberg & Silverberg;1986). Wang and Wildman (1995), Thomas (1986), Lockheed, Fuller, and Nyirongo (1989), Staver and Walberg (1986), and Maple and Stage (1991) reported that parental support behaviors related to science significantly contributed to science achievement and choice of science-oriented careers. In the present study, we examine further the relationship between parental and student attitudes.…”
Section: Parents and Attitudesmentioning
confidence: 94%